Evangelizing Dimension „Instrucción de la orden que se ha de tener en la doctrina de los naturales” from the Year 1545, by Bishop Kerónimo de Loaysa from Lima - Szyszka, Tomasz (Studia Warmińskie, 2011)
Over a dozen years since the beginning of evangelization of Andean world, in year 1545 the first bishop of Lima Jeronimo de Loaysa issued Instruccion de la orden que se de tener en la doctrina de los natrurales. In this document he presented his notion about the ways and methods how to evangelize autochthons. This instruction was addressed to all missionaries who were involved in evangelizing Indians. In eighteen chapters of this instruction were presented the following questions: problem of freedom in converting local Indians to Christianity, issue of administering of sacraments to Indians, the basic catechesis, importance of sacral buildings and legal regulations concern marriage arrangement, keeping fasts and celebrations of Church’s feasts. Content of this document was placed in the final document of the First Synod of Lima from year 1552. Directives of bishop Loaysy from the year 1545 showed the directions and main concepts of evangelization of Indians in South America during the colonial period.